Analisis Perbedaan Mutu Udang Vannamei (Litopenaeus vannamei) Segar Menggunakan Perendaman Larutan Ekstrak Buah dan Daun Mangrove (Rhizophora mucronata) : Analysis of Quality Differences in Fresh Vannamei Shrimp (Litopenaeus vannamei) Treated with a Soaking Solution of Mangrove (Rhizophora mucronata) Fruit and Leaf Extracts - Tahuru, Afidtriadi; Rita Marsuci Harmain, Rita; Mile, Lukman (Media Teknologi Hasil Perikanan, 2026)
Vannamei shrimp (Litopenaeus vannamei) is one of the leading non-fish commodities in Gorontalo Province. Alternative post-harvest treatments to maintain the quality of fresh vannamei shrimp can be obtained from the mangrove plant Rhizophora mucronata. The objectives of this study were to analyse the hedonic quality of fresh vannamei shrimp using extracts from the fruit and leaves of R. mucronata mangroves during the soaking period; analysing the hedonic, chemical, and microbiological quality of the best mangrove solution extract during the soaking period; and analysing the hedonic quality of the mangrove solution extract during storage at room temperature. The hedonic quality method was based on a fresh shrimp quality score sheet completed by 25 semi-trained panelists. Data processing used the non-parametric Kruskal-Wallis statistic. Chemical (pH) and microbiological (Total Plate Count (TPC)) quality testing used a non-factorial completely randomised design. The treatments consisted of 0 hours (F1), 3 hours (F2), 6 hours (F3) and 9 hours (F4) with 3 (three) replicates. Analysis of variance (ANOVA) was performed using Statistical Package For Social Science 16 (SPSS 16). The results of hedonic, chemical (pH) and microbiological (TPC) quality analyses, if significant, were followed by Duncan's test and processed descriptively and quantitatively. The results showed that mangrove leaf extract solution was more effective in maintaining the quality of vannamei shrimp for up to 6 hours of immersion. The pH value tends to fluctuate but remains within a safe range, and the number of microbes (Total Plate Count) is still below the safe limit of Indonesian National Standard 01-2728.1-2006 on the quality of fresh shrimp up to 6 hours of immersion. Based on the results of hedonic quality tests, the longer the storage time at room temperature, the greater the decline in the quality of fresh vannamei shrimp. Keywords:    quality, soaking, storage, Rhizophora mucronata, Vannamei shrimp Udang vannamei (Litopenaeus vannamei) sebagai salah satu komoditas unggulan non ikan di Propinsi Gorontalo. Alternatif penanganan pascapanen untuk mempertahankan mutu udang vannamei segar dapat diperoleh dari tumbuhan mangrove Rhizophora mucronata Tujuan penelitian adalah menganalisis mutu hedonik udang vannamei segar menggunakan ekstrak larutan buah dan daun mangrove R.mucronata selama waktu perendaman; menganalisis mutu hedonik, kimia dan mikrobiologi ekstrak larutan mangrove terbaik selama waktu perendaman; dan menganalisis mutu hedonik ekstrak larutan mangrove selama waktu penyimpanan pada suhu ruang. Metode mutu hedonik berdasarkan scorsheet mutu udang segar sebanyak 25 panelis semi terlatih. Pengolahan data menggunakan statistik non parametrik Kruskal Wallis. Pengujian mutu kimia (pH) dan mikrobiologi (Total Plate Count (TPC)menggunakan Rancangan Acak Lengkap Non Faktorial. Perlakuan terdiri dari 0 jam (F1), 3 jam (F2), 6 jam (F3) dan 9 jam (F4) sebanyak 3 (tiga) kali ulangan. Analisis ragam (ANOVA) menggunakan Statistical Package For Social Science 16 (SPSS 16). Hasil analisis mutu hedonik, kimia (pH) dan mikrobiologi (TPC) jika signifikan dilanjutkan dengan uji Duncan dan diolah secara deskriptif kuatitatif. Hasil penelitian menunjukkan bahwa ekstrak larutan daun mangrove lebih mampu mempertahankan mutu udang vannamei hingga 6 jam perendaman. Nilai pH cenderung berfluktuasi tetapi tetap dalam rentang aman, dan jumlah mikroba (Total Plate Count) masih di bawah batas aman Standard Nasional Indonesia 01-2728.1-2006 tentang mutu udang segar hingga jam ke-6 perendaman. Larutan ekstrak daun mangrove pada udang vannamei selama penyimpanan pada suhu ruang berdasarkan hasil uji mutu hedonik diperoleh bahwa semakin lama waktu penyimpanan pada suhu ruang terjadi penurunan mutu udang vannamei segar. Kata Kunci: Mutu; Perendaman; Penyimpanan, Rhizophora mucronata; Udang vannamei